2022
DOI: 10.2147/ijgm.s369582
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the E2F Transcription Factor Family in Human Lung Adenocarcinoma

Abstract: Background E2F transcription factors (E2Fs), code a family of pivotal transcription factors, have been identified as key regulators in tumor tumorigenesis. However, the function of E2F family in human lung adenocarcinoma (LUAD) have not been fully elucidated. Methods Herein, The Cancer Genome Atlas (TCGA) databases, Kaplan-Meier plotter, cBioPortal and TIMER were used to analyze differential expression, prognostic value, genetic alteration and immune cell infiltration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In fact, previous studies have found that E2F1 expression was elevated in tumor tissues and associated with the poor prognosis of cancer. The expression levels of E2Fs (E2F1-8) were all significantly up-regulated in LUAD tissues [ 14 ], Wang et al investigated the expression, prognosis value, mutation, and potential relationship with immunological aspects of E2Fs in LUAD by bio-informatics analysis [ 14 ].E2F1 is expressed strongly in 59.8% of ESCC and that the over-expression was correlated with tumor progression, lymph node metastasis, and poor prognosis after surgery [ 16 ]. Over-expression of E2F1 was significantly associated to worsen OS in all NSCLC patients followed for 200 months, as well as in LUAD patients [ 26 ],which was duplicated in HCC patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, previous studies have found that E2F1 expression was elevated in tumor tissues and associated with the poor prognosis of cancer. The expression levels of E2Fs (E2F1-8) were all significantly up-regulated in LUAD tissues [ 14 ], Wang et al investigated the expression, prognosis value, mutation, and potential relationship with immunological aspects of E2Fs in LUAD by bio-informatics analysis [ 14 ].E2F1 is expressed strongly in 59.8% of ESCC and that the over-expression was correlated with tumor progression, lymph node metastasis, and poor prognosis after surgery [ 16 ]. Over-expression of E2F1 was significantly associated to worsen OS in all NSCLC patients followed for 200 months, as well as in LUAD patients [ 26 ],which was duplicated in HCC patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…During article searching, two essays [ 14 , 15 ] regarding to lung adenocarcinoma (LAUD) and lung squamous cell carcinoma (LUSC) were from the same database as an included article [ 15 ] on lung cancer (LC). In order to prevent repeated inclusion of data, we have deleted the above two essays.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, previous studies have found that E2F1 expression was elevated in tumor tissues and associated with the poor prognosis of cancer. The expression levels of E2Fs (E2F1-8) were all signi cantly upregulated in LUAD tissues [13], Wang et al investigated the expression, prognosis value, mutation, and potential relationship with immunological aspects of E2Fs in LUAD by bio-informatics analysis [13].E2F1 is expressed strongly in 59.8% of ESCC and that the over-expression was correlated with tumor progression, lymph node metastasis, and poor prognosis after surgery [15]. Over-expression of E2F1 was signi cantly associated to worsen OS in all NSCLC patients followed for 200 months, as well as in LUAD patients [24],which was duplicated in HCC patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…During article searching, two literatures [13,14] regarding to lung adenocarcinoma (LAUD) and lung squamous cell carcinoma (LUSC) were from the same database as an included article [14] on lung cancer (LC). In order to prevent repeated inclusion of data, we have deleted the above two literatures.…”
Section: Data Extraction and Checkingmentioning
confidence: 99%
“…ICD-related genes ENTPD1, NT5E, CALR, HMGB1, HSP90AA1, ATG5, BAX, CASP8, PDIA3, EIF2AK3, PIK3CA, CXCR3, IFNA1, IFNB1, IL10, IL6, TNF, CASP1, IL1R1, IL1B, NLRP3, P2RX7, LY96, MYD88, TLR4, CD4, CD8A, CD8B, FOXP3, IFNG, IFNGR1, IL17A, IL17RA, and PRF1 summarized by Abhishek et al 20 . Common immune checkpoints include CD274, CTLA4, HAVCR2, LAG3, PDCD1, PDCD1LG2, SIGLEC15, and TIGIT 21 . The R software package ggplot2 (v3.3.3) was used to plot scatter plots, correlation heat maps, lollipop diagrams, and calculate correlation coefficients.…”
Section: Methodsmentioning
confidence: 99%